A survey of guidance, navigation, and control systems for autonomous multi-rotor small unmanned aerial systems. (2021) - Marshall, Julius A.; Sun, Wei; L'Afflitto, Andrea
Abstract: This survey paper presents a holistic perspective on the state-of-the-art in the design of guidance, navigation, and control systems for autonomous multi-rotor small unmanned aerial systems (sUAS). By citing more than 300 publications, this work recalls fundamental results that enabled the design of these systems, describes some of the latest advances, and compares the performance of several techniques. This paper also lists some techniques that, although already employed by different classes of mobile robots, have not been employed yet on sUAS, but may lead to satisfactory results. Furthermore, this publication highlights some limitations in the theoretical and technological solutions underlying existing guidance, navigation, and control systems for sUAS and places special emphasis on some of the most relevant gaps that hinder the integration of these three systems. In light of the surveyed results, this paper provides recommendations for macro-research areas that would improve the overall quality of autopilots for autonomous sUAS and would facilitate the transition of existing results from sUAS to larger autonomous aircraft for payload delivery and commercial transportation.